2018
DOI: 10.1001/journalofethics.2018.20.1.stas1-1801
|View full text |Cite
|
Sign up to set email alerts
|

Continuing Medical Education and Firearm Violence Counseling

Abstract: Firearm violence is a significant and increasing cause of mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Lack of knowledge is cited by physicians as a primary barrier to firearm counseling in a clinical setting [ 12 ]. Groups such as the American College of Physicians [ 17 ], California Medical Association [ 18 ], and American Academy of Pediatrics [ 19 ] support physician screening for firearm violence prevention, and research suggests that 65 to 93 percent of physicians recognize firearm counseling as within a physician’s scope of practice [ 20 ]. Physicians may need education and training on firearm injury prevention in order to incorporate it into their practices.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of knowledge is cited by physicians as a primary barrier to firearm counseling in a clinical setting [ 12 ]. Groups such as the American College of Physicians [ 17 ], California Medical Association [ 18 ], and American Academy of Pediatrics [ 19 ] support physician screening for firearm violence prevention, and research suggests that 65 to 93 percent of physicians recognize firearm counseling as within a physician’s scope of practice [ 20 ]. Physicians may need education and training on firearm injury prevention in order to incorporate it into their practices.…”
Section: Introductionmentioning
confidence: 99%
“…A prior study found that family physicians who received formal training on firearm safety counseling reported greater comfort in asking their patients about firearms ( 17 ). A survey of North Carolina physicians revealed that few had attended continuing medical education events on gun violence, but participation in such events was strongly associated with providing patient firearm counseling often or very often ( 31 ). Accordingly, the development of educational programs for health care professionals caring for persons with TBI addressing firearm injury prevention may be an appropriate strategy to improve their training and comfort in the provision of this education and the likelihood they will provide it.…”
Section: Discussionmentioning
confidence: 99%
“…Firearm-related homicide is the leading cause of death among African American males ages 15 to 24, the largest population represented in our study (Centers for Disease Control and Prevention, 2020). Barriers to firearm screening include lack of training, time constraints, and concern for personal safety (Damari et al, 2018., Fein et al, 2000). Additionally, in the busy ED setting, many providers may assume that other members of the care team, including a social worker or consultant, may screen patients for firearm access.…”
Section: Discussionmentioning
confidence: 99%